A novel ex vivo high-throughput assay reveals antiproliferative effects of idelalisib and ibrutinib in chronic lymphocytic leukemia - Primo, Daniel (Oncotarget, 2018)
PI3Kδ (idelalisib) and BTK (ibrutinib) inhibitors have demonstrated significant clinical activity in chronic lymphocytic leukemia (CLL) interfering with the cross-talk between CLL cells and the lymph node microenviroment, yet their mechanism of action remains to be fully elucidated. Here, we developed an ex vivo model with the aim of reproducing the effects of the microenvironment that would help shed light on the in vivo mechanism of action of idelalisib and ibrutinib and predict their clinical efficacy in individual patients. First we explored the effects of various cell-extrinsic elements on CLL apoptosis and proliferation and found that the combination of CpG+IL2+HS5 stromal cell line + human serum +CLL plasma and erythrocyte fractions represented the best co-culture conditions to test the effects of the novel inhibitors. Then, using this assay, we investigated the impact of idelalisib and ibrutinib on both survival and proliferation in 30 CLL patients. While both drugs had a limited direct pro-apoptotic activity, a potent inhibition of proliferation was achieved at clinically achievable concentrations. Notably, up to 10% of CLL cells still proliferated even at the highest concentrations, likely mirroring the known difficulty to achieve complete responses in vivo. Altogether, this novel assay represents an appropriate ex vivo drug testing system to potentially predict the clinical response to novel inhibitors in particular by quantifying the antiproliferative effect.